A Critical Discourse Analysis of NBC News Entitles' Anti-Asian Hate Incident Reports Nearly Doubled in March, New Data Says' - Annisa Indah Sukma; Zakie Asidiky (English Department - University of Sultan Ageng Tirtayasa, 2022)
This research aimed to critically discover the author's ideology in the text entitled